Modelos gerenciales en la administración educativa - Vargas Jiménez, Ileana (2004)
Analysis of various management models that account for organizational behavior and of how these models affect—positively or negatively—the work carried out in educational institutions. The theory and its functions are defined to serve as a basis to the analysis. The paper finishes mentioning the model for the management of quality circles and how it can influence on decision-making processes at educational institutions.